Pengaruh Pemasaran Media Sosial terhadap Niat Beli Ulang Melalui Perceived Value Konsumen Produk Skintific : Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Negeri Makassar - My Sarah Imran; Anwar Ramli; Siti Hasbiah; Isma Azis Riu; Rahmat Riwayat Abadi (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to analyze the effect of social media marketing on repurchase intention of Skintific products through perceived value by consumers, especially among students of the Faculty of Economics and Business, Makassar State University. The type of research used in this study is quantitative research with an explanatory approach. The population in this study consisted of active students who use Skintific products, with a sample of 150 respondents selected using purposive sampling technique. Data collection was carried out through a Likert scale-based questionnaire distributed to respondents. The data collected is then processed using the SmartPLS 3.2.9 analysis tool and this research method uses Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results showed that social media marketing has a positive and significant influence on repurchase intentions. In addition, social media marketing also has a positive and significant effect on consumer perceived value. Perceived value of consumers is also proven to have a positive and significant effect on repurchase intentions. Further analysis shows that perceived value acts as a significant mediator in the relationship between social media marketing and repurchase intentions.